Fabrication of Graphene Oxide/Calcium Carbonate/Chitosan Nanocomposite Film with Enhanced Mechanical Properties. (September 2019) - Handayani, M; Sulistiyono, E; Rokhmanto, F; Darsono, N; Fransisca, P L; Erryani, A; Wardono, J T
Abstract: Nanocomposites are an attractive field of materials providing novel performance owing to their remarkable properties at low filler loading. Currently, they are being increasingly used by industry whilst displacing the use of conventional filler materials. A lot of nanoscale fillers are capable to enhance mechanical and thermal properties of nanocomposites. Graphene, a single layer of carbon atoms in a hexagonal lattice, has recently attracted much attention due to their novel electronic and mechanical properties. Graphene and graphene oxide show very high mechanical properties with well biocompatibility, and they have potential application as biomaterials. Therefore, 2D graphene or graphene oxide sheets are expected to offer promising nanoscale filler for the next generation of nanocomposite materials. Here, Graphene Oxide/Calcium Carbonate/Chitosan (GO/CaCO3 /CS) Nanocomposite Film has been fabricated by the blending aqueous solution. The graphene oxide used in this study was synthesized by chemical way from pure graphite using modified hummer's technique. The graphene oxide resulted from hummer's method was characterized by IR, XRD and SEMEDX. The measurement result of the mechanical properties of the nanocomposite film showed that with adding GO content in the composite enhanced the tensile strength and peaks at the content of GO 5 % due to good dispersion of the graphene oxide as nano-scale fillers.